Does oil consumption promote economic growth in oil producers? - Fuinhas, José Alberto (2019)
Purpose – The oil-growth nexus is studied in a panel of Organization of the Petroleum Exporting Countries (OPECs), for a long time span (1960-2011), controlling for the specific context of oil production. Their membership in the cartel put them under a common guidance, which originates phenomena of cross-section dependence/contemporaneous correlation in the panel. Design/methodology/approach – Recent panel data estimators and co-integration analyses are both pursued and discussed, namely, dealing with the heterogeneity of panels and the countries’ specific effects. The Driscoll–Kraay estimator proves to be appropriate in handling the panel properties. Findings – Full understanding of the oil-growth nexus requires the short- and long-run effects to be broken down. The growth hypothesis was found only in the short run. The results suggest the presence of the resource curse phenomenon and prove that the cartel’s long-run growth goal could not being fully accomplished. Actually, both oil production and prices are not promoting economic growth in OPEC countries. Originality/value – The focus is on a group of countries which, besides being oil exporters, have na institutional connection between them, i.e. the OPEC cartel. The paper also contributes by framing the relationship between oil consumption and economic growth within a context of countries that are primary energy producers. Additionally, the paper uses a novel econometric approach and a long time span (52 years) not tested